KEBIJAKAN PROYEK OPERASI NASIONAL AGRARIA (PRONA) DALAM RANGKA MEWUJUDKAN TERTIB ADMINISTRASI PERTANAHAN DI KOTA PEKANBARU - Siregar, Giovanni Aristha; Tua R.F.S, Harapan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The ground is supporting the welfare and prosperity of the whole society of indonesia, because the ground has a major role both in the industrial sector and agricultural sector. Because almost all of human utility comes from ground, then human race the race to have the ground. Things related to the ground included in the constitution of the republic of Indonesia year 1945. See the importance of ground as a human life support, so the research is based on human needs for the ground and the importance of having a ground certificate for the whole society including the economically weak to medium. PRONA Policy is a public policy made by Indonesia government as one of the efforts in achieving orderly ground administration in the entire territory of indonesia. The implementation of the PRONA Policy is also implemented in the Pekanbaru see there are still many ground that is not owner. To realize the orderly administration of the ground throughout the territory of Pekanbaru the government is implementing a PRONA Policy is in accordance with the provisions of laws and regulations. The PRONA Policy aims to provide ground registration services the first time with a simple process, easy, quick and cheap in order to accelerate the ground registration throughout the territory of Indonesia.This research uses the qualitative research method which obtains data through observation, interviews and documentation. In this research the writer uses Donald S. Van Meter and Carl E. Van Horn theory with the analysis of descriptive data qualitative that reveals the genesis or the fact, situation, phenomenon, variable and circumstances that occur during the research by presenting what actually happened. This research interprets and describes the data concerned with the situation that is happening, attitudes and views that occur in a society, a conflict between two states or more, relationship between variable that arise, difference between the facts and its influence on a condition and so on.After the writer conducted the research in the ground office national ground agency of pekanbaru city (BPN) the writer can take conclusion that during the last five years of the implementation of the PRONA Policy in the Pekanbaru has been running pretty optimal. Although still found some obstacles in implementation, such as communication that are less good and lack of society participation because the lack of information derived by the public from BPN Pekanbaru city about PRONA Policy.Keywords: Policy, Public Policy, Ground affairs, The orderly administration